Dickens's comic art: a study of the comic element in Dombey and Son, Little Dorrit, and Great Expectations - McBride, Ian Nicholas (Department of English Language and Literature, 2016)
It is my contention in this thesis that the comic nature of Dickens's mature fiction has not received the degree of attention that its importance warrants. In particular, the questions left unanswered, or to my mind not satisfactorily answered, by modern critics of Dickens are: why does Dickens consistently adopt modes of comedy in his mature works; what are the modes that he adopts; and what are the implications of these modes in terms of his later achievement? Finally, in what way can his vision be judged to be a comic vision?